An investigation of the Plasmodium falciparum malaria epidemic in Kavango and Zambezi regions of Namibia in 2016. (25th September 2018) - Chanda, Emmanuel; Arshad, Mohd; Khaloua, Asmaa; Zhang, Wenyi; Namboze, Josephine; Uusiku, Pentrina; Angula, Andreas H; Gausi, Khoti; Tiruneh, Desta; Islam, Quazi M; Kolivras, Korine; Haque, Ubydul
Abstract: Background: Namibia is one of the countries among the eight that are targeting malaria elimination in southern Africa. However, the country has encountered malaria epidemics in recent years. The objective of this study was to investigate malaria epidemics and to contribute to strengthening malaria surveillance and control in an effort to move Namibia toward eliminating malaria. Method: Malaria epidemiology data for 2014–2015 were collected from the weekly surveillance system. All consenting household members within a 100-m radius of index households were screened in 2016 using a Carestart malaria HRP2/pLDH combined rapid diagnostic test after epidemics. All houses within this radius were sprayed in 2016 with the pyrethroid deltamethrin and K-Othrine WG 250. Anopheles mosquito–positive breeding sites were identified and treated with the organophosphate larvicide temephos. Insecticide susceptibility and bioassay tests were conducted. Results: During the epidemic response period in 2016, 56 parasitologically confirmed Plasmodium falciparum malaria cases in the Zambezi region were detected from active screening. The majority of those cases (83%) were asymptomatic infections. In the Kavango region, the malaria epidemic persisted, with 228 P. falciparum malaria cases recorded, but only 97 were investigated. In Namibia, malaria vector susceptibility was detected to 4% dichlorodiphenyltrichloroethane. Indoor residual spraying was conducted in 377 (90%) of the targeted households along with community awareness through health education of 1499 people and distribution of more than 2000 information, education and communication materials. The P. falciparum malaria cases in the Zambezi decreased from 122 in week 9 to 97 after week 15. Conclusions: Malaria epidemics along with the persistence of asymptomatic reservoir infections pose a serious challenge in Namibia's elimination effort. The country needs to ensure sustainable interventions to target asymptomatic reservoir infections and prevent epidemics in order to successfully achieve its goal of eliminating malaria.